PENGEMBANGAN MEDIA LUDO GAME BERBANTUAN GENIALLY PADA TOPIK APA DAN UNTUK APA MAGNET DICIPTAKAN - kharima sekarayu; Lina Novita; Fitri Anjaswuri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Kharima Sekar Ayuni. 037121021. Pengembangan Media Ludo Game Berbantuan Genially Pada Topik Apa Dan Untuk Apa Magnet Diciptakan. This research employed a Research and Development (R&D) approach at SDN Cipari Kabupaten Bogor. The research subjects included validators consisting of 4 expert validators and 38 fifth-grade students of class V-B at SDN Cipari, Kabupaten Bogor. The study was conducted in the second semester of the 2024/2025 academic year. The percentage results from the experts were as follows: media expert 96%, language expert 94%, material expert (lecturer) 84%, and material expert (teacher) 98%. The percentage results for student responses were 97%, and teacher responses were 100%. Therefore, it can be concluded that Pengembangan Media Ludo Game Berbantuan Genially Pada Topik Apa Dan Untuk Apa Magnet Diciptakan is declared valid or very feasible to be implemented in the fifth grade of Elementary School. The findings of this research are expected to provide new knowledge regarding Genially-assisted Ludo Game media, thereby creating a fun and engaging learning environment for students, preventing boredom.